Factors Affecting Individual Investors’ Stock Investment Decision in Nepal - Rana, Surya Bahadur (Tribhuvan University Journal, 2019)
This paper attempts to explore the factors associated with individual investors’ stock investment decision in the context of stock market in Nepal. The study also aims to examine the relative importance of investment decision factors as perceived by investors based on their demographic characteristics. The study uses a sample responses of 106 individual investors obtained through structured questionnaire survey during the period January to April, 2019. The study employs exploratory factor analysis to extract the common factors affecting stock investment decisions of the sample investors. The results of factor analysis show that six factors, namely Earnings and Image Factors, Corporate Governance and Positioning Factors, Goodwill and Market Share Factors, Industry Competition and Size Factors, Fundamental Market Factors, and Decision Making Factors are the common factors affecting stock investment decision of the sample investors in Nepal. The results also show that among the six factors extracted, Fundamental Market Factors have high relative importance as perceived by the sample investors.